2015
DOI: 10.1007/s11126-015-9371-5
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Abuse and Mental Health Problems: Does Gender Matter?

Abstract: Gender differences in the relationship between mental health problems and childhood abuse have long been of interest to researchers. The purpose of the present study was to examine gender differences in the relationship between childhood abuse and mental health problems among 110 Israeli inmates (50 women and 60 men). The findings indicated that female inmates reported higher prevalence of physical, emotional, and sexual abuse and were more likely to suffer from mental health problems, compared with the male i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 65 publications
3
8
0
Order By: Relevance
“…More females report current mental health needs than males in our study. While this finding corroborates those of previous studies [52, 53], literature also suggests that males are less likely than females to recognize and report their mental health needs and, as a result, rarely access mental health services and treatment [54–56]. It is critical to further understand gender-specific mental health needs as well as help-seeking patterns and decision process, so that targeted strategies that encourage service utilization can be developed.…”
Section: Discussionsupporting
confidence: 85%
“…More females report current mental health needs than males in our study. While this finding corroborates those of previous studies [52, 53], literature also suggests that males are less likely than females to recognize and report their mental health needs and, as a result, rarely access mental health services and treatment [54–56]. It is critical to further understand gender-specific mental health needs as well as help-seeking patterns and decision process, so that targeted strategies that encourage service utilization can be developed.…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence of emotional abuse and neglect were higher among women (7.5% and 31.1% respectively) than men (4.5% and 24.0% respectively). Previous reports indicated that female alcohol abusers (Bailey, Baker, Mcelduff, & Kavanagh, 2016) and female inmates (Chen & Gueta, 2016) were more likely than males to experience emotional abuse or neglect. A study also found that female high school students who experienced emotional/sexual abuse had a higher prevalence of lifetime opioid use than male students in China (Lei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The current research was part of a larger project conducted by the authors that included mixed methods research in Israeli prisons (Chen and Gueta 2016). The committee of the Israel Prison Service approved the project and instructed the prison directors to collaborate with the researchers.…”
Section: Methodsmentioning
confidence: 99%